Improving Fluid Output Monitoring in the Intensive Care Unit. (January 2022) - Kushnir, Alexander; Palte, Eytan; Morris, Nadia; Shahabuddin, Zoha A.; Hammond, Jeffrey; Vukelic, Sinisa; Rabbani, LeRoy E.
Purpose: To assess the potential clinical impact of an automated urine output (UOP) monitoring system in the intensive care unit. Methods: Frequency of UOP documentation during a 20-month period was assessed in records of inpatients on the medicine floor, cardiac intensive care (CCU), and cardiothoracic-intensive care units (CTICU). Documentation timeliness (time between expected and observed UOP recording) was assessed over a 3-month period. A novel reusable device that monitors UOP based on continuous analysis of the weight of a urine collection container was tested in the CCU/CTICU. Results: A total of 165, 363 UOP measurements were recorded for 2, 039 CCU/CTICU admissions. Sixty percent of CCU/CTICU admissions had UOP recorded in the electronic medical record (EMR) less than every 2 hours. One-third of CCU/CTICU measurements were documented more than 2 hours late, and only 10% were recorded less than 20 minutes late. Half of these patients had fewer than 2 measurements recorded per nursing shift and recordings were documented an average of 85 minutes late. There was no significant difference between daytime and nighttime shifts. UOP values obtained by the novel electronic monitoring device were within 27 ml (−224 ml, +228 ml) of nurses documented values, across 74 patients over a 24-hour period. Conclusions: Automating UOP monitoring using a reusable weight-based device is feasible and can improve timeliness of documentation and reduce nursing workload without compromising accuracy.